Efecto de extractos crudos de cordyceps takaomontana cultivado en medios naturales en la actividad enzimática de pleurotus ostreatus para la degradación de lignina (2016)
At present, the use of fungi that produce lignin-degrading enzymes had been studied as a biological pre-treatment of vegetal biomass, which has caught especial attention as replacement of petroleum. These organisms facilitate the fermentable sugars sourcing for biofuels production. Lignocellulosic biomass mainly consists of three polymers: cellulose, hemicellulose, and lignin. This last one is a compound that provides structural support and hinders the degradation of cellulose and hemicellulose, which are reduced to the fermentable sugars. Pleurotus ostreatus is an edible white-rot fungus which can be used in the pre-treatment of the vegetal biomass. It has been reported that the intervention of metabolites, such as nucleosides, in the metabolic pathway of fungi can enhance the production of hydrolytic enzymes. In the following study, we analysed the effects of the crude extract of Cordyceps takaomontana grown on natural culture media as enhancers or repressors of laccase activity of Pleurotus ostreatus for lignin-degrading process of rice husks. Cordyceps takaomontana were cultured in two different natural substrates: butterfly pupa agar and brown rice agar, the metabolites were extracted with three solvents: water, methanol, and n-hexane. Then, the extracts were mixed with the pre-inoculum of P. ostreatus and finally added to the rice husk, which is the substrate selected to monitor the amount of glucose and laccases. The effect of the metabolites was determined by response variables: amount of glucose and enzymatic activity by spectrophotometry using ABTS. It was established that the metabolites of Cordyceps takaomontana grown in brown rice suppress the enzymatic activity of Pleurotus ostreatus. On the other hand, it was determined that the solvent that encourages the lignin-degrading activity of Pleurotus ostreatus is water because it efficiently extracts the polar metabolites. From these results, we recommended to use the metabolites extracted with water.